2014
DOI: 10.3389/fnhum.2014.00924
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing inferential abilities in adolescence: new hope for students in poverty

Abstract: The ability to extrapolate essential gist through the analysis and synthesis of information, prediction of potential outcomes, abstraction of ideas, and integration of relationships with world knowledge is critical for higher-order learning. The present study investigated the efficacy of cognitive training to elicit improvements in gist reasoning and fact recall ability in 556 public middle school students (grades seven and eight), vs. a sample of 357 middle school students who served as a comparison group, to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
19
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 65 publications
7
19
0
1
Order By: Relevance
“…The finding of improved synthesising ability is encouraging, since it has not been previously documented that impaired abstraction of complex information skills can be improved years after sustaining a brain injury in those with persistent mild deficits. These findings extend prior work showing that SMART's utilisation of multi-dimensional thinking strategies serves to improve the ability to synthesise information in healthy adults, teens with chronic-stage TBI, and teens living in poverty (Anand et al, 2011;Cook et al, 2014;Gamino et al, 2014;Vas et al, 2011). The present evidence suggests that the SMART programme has the potential to enhance higher-order abstract thinking capacity in adults with mild-spectrum TBI (who constitute the majority of the TBI population).…”
Section: Gist Reasoningsupporting
confidence: 82%
See 1 more Smart Citation
“…The finding of improved synthesising ability is encouraging, since it has not been previously documented that impaired abstraction of complex information skills can be improved years after sustaining a brain injury in those with persistent mild deficits. These findings extend prior work showing that SMART's utilisation of multi-dimensional thinking strategies serves to improve the ability to synthesise information in healthy adults, teens with chronic-stage TBI, and teens living in poverty (Anand et al, 2011;Cook et al, 2014;Gamino et al, 2014;Vas et al, 2011). The present evidence suggests that the SMART programme has the potential to enhance higher-order abstract thinking capacity in adults with mild-spectrum TBI (who constitute the majority of the TBI population).…”
Section: Gist Reasoningsupporting
confidence: 82%
“…However, all participants reported difficulty in returning to pre-TBI levels of work ability and/or obtaining gainful employment as a result of cognitive difficulties in their initial interview. We did not base inclusion on gist performance since prior training studies have shown improvement in gist reasoning, executive function capacities and frontal networks with similar training in healthy adults and teens Gamino et al, 2014).…”
Section: Methods Participantsmentioning
confidence: 99%
“…Todos los informes (Caraballo, García, Javier, Lara, & Mateo, 2016;EDUCA-PREAL, 2010) recomiendan la necesidad de continuar ampliando la cobertura en el Nivel Inicial y ofrecer más años de escolarización, sobre todo en los sectores más vulnerables. Pero si el acceso, no se acompaña de programas de calidad y de otros apoyos que permitan mitigar los efectos de la pobreza en los niños y en sus contextos, no habrá esperanza para los adolescentes del futuro (Gamino et al, 2014), y como lo establece Luby et al, (2013), esto debe ser rápido, pues el desarrollo no tiene tiempo para esperar.…”
Section: Discusión Y Conclusionesunclassified
“…For example, studies in the United States have shown that cognitive training significantly increased ''gist reasoning'' 14 (e.g. Gamino et al 2014). Similarly, several programmes implemented in economically prosperous countries increase creative thinking in specific domains (see Abadzi et al 2014 for a review).…”
Section: Formation Of Non-cognitive Skillsmentioning
confidence: 99%